Halal Awareness in Food Purchasing Decisions: A Systematic Review of the Literature 2019-2024: Kesadaran Halal Dalam Keputusan Pembelian Makanan: Kajian Sistematik Literatur 2019-2024 - Eko Raharto (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
Halal food awareness is an understanding that a person or consumer has about consuming halal food, which usually influences interest and purchasing decisions, among the ways to increase halal awareness is by increasing the level of religiosity. This Systematic Literature Review study aims to determine the themes of research studies on the topic of halal awareness in the period 2019-2024. This type of research uses a Systematic Literature Review (SLR) study through 3 stages, namely pre-selection (identification), selection, and determination of articles that meet the criteria. The results of the study show that there are 3 main themes or topics of discussion in this study, namely (1) study of themes based on the type of research, (2) study of themes based on the religion or beliefs of respondents (Muslim and non-Muslim), and (3) study of the role of halal awareness in influencing other variables, and moderating or mediating in consuming halal food. For further research, it is recommended to be more specific in determining respondents between Muslims and non-Muslims (not mixed) and the use of mix method research (qualitative-quantitative).